Reformasi Kebijaksanaan Dalam Manajemen Lingkungan Perkotaan - B. Kombaitan (Journal of Regional and City Planning, 1995)
Formulating the right answer to the issue of rapid urban growth and degradation in urban environmental quality that ¡s related to the problem of urban productivity and poverty has become the ultimate challenge facing the urban and environmental planner in the third world. Difficult enough, because other than the classic problems of inter sectoral priority, it also has economic and political implications. Worse than these, local environmental problems are rarely understood by that local government. The effort to handle urban environmental problem should be approached from two stages of activities. First, is the needs to understand the problem and to find the solution. Second, is the need to have reformation to formulate urban environmental management and its implementation.